ZIPRASIDONE HYDROCHLORIDE LOADED NANOSTRUCTURED LIPID CARRIERS (NLCS) FOR INTRANASAL DELIVERY: OPTIMIZATION AND IN VIVO STUDIES - SIVADASU, PRAVEEN; D. V., GOWDA; H., SIDDARAMAIAH; S., HEMALATHA (International Journal of Applied Pharmaceutics, 2020)
Objective: The present study was an attempt to systemically deliver the most desirable schizophrenia drug, ziprasidone hydrochloride (ZRS) via the intranasal route using nanostructured lipid carrier (NLC) approach. Methods: The desired ZRS loaded NLCs were developed using central composite statistical design and the developed formulation was monitored for improving ZRS bioavailability and their brain targeting efficacy. Results: Pharmacokinetic studies revealed a 10 fold increase (ZRS blood-brain ratio) for NLCs administered through nasal route (in comparison to intravenous route). Similarly, the concentration of ZRS (in the brain) delivered via nasal route exhibits 4 fold increment at all-time points. Conclusion: Therefore, the obtained results suggest a potential nose to brain transport of loaded ZRS by effective bypassing of the Blood-Brain Barrier (BBB).